Chemoradiation, Consolidation Chemotherapy, and Watch and Wait for Early Rectal Cancer - Cerdan-Santacruz, Carlos; São Julião, Guilherme Pagin; Vailati, Bruna Borba; Perez, Rodrigo Oliva (Clinics in Colon and Rectal Surgery, 2023)
As watch and wait has become an attractive management alternative among patients with rectal cancer who achieve a clinical complete response to neoadjuvant chemoradiation, the focus of organ preservation has now shifted toward the use of this approach in patients with early rectal cancer. These patients would otherwise be treated without the use of neoadjuvant therapy for oncological reasons. The sole purpose of any neoadjuvant treatment here would be the achievement of a complete clinical response in an attempt to avoid total mesorectal excision. This has become particularly interesting after the incorporation of total neoadjuvant therapy regimens. These regimens have resulted in significantly higher rates of complete tumor regression and therefore become an interesting alternative among early rectal cancer patients where organ preservation is desired. The present review provides an overview of the currently available evidence and the preliminary experience with this rather controversial approach.
Keywords: rectal cancer; chemoradiation; radiation; total neoadjuvant therapy; watch and wait